Effectiveness of Ketapang Leaf Extract (Terminal Capta L) in Water Media on Crude Egg Hatching - Buana Basir; Kaharuddin Kaharuddin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
Ketapang leaves are one of the leaves that are already known bioactive materials contained therein which can be utilized in aquaculture media. This study aims to analyze the use of ketapang (Termianal capta L.) leaf extract in water media on the hatchability of cork fish eggs (Channa striata). The research is expected to provide knowledge about the benefits of ketapang leaves in aquaculture media and the hatchability of cork fish eggs. The study was conducted at the Fish Seed Center (BBI) Bantimurung, Maros Regency. The test sample came from BBI Bantimurung. The study used 4 experimental methods with 3 replications each addition of ketapang leaf extract on water media, namely media without ketapang leaf extract (A), the addition of ketapang leaf extract 10 ppm (B), the addition of ketapang leaf extract 20 ppm (C), addition of 30 ppm ketapang leaf extract (D). The results showed that the treatment significantly affected the hatchability of cork fish eggs. The highest average hatchability of eggs in treatment D with a concentration of ketapang leaf extract was 30 ppm. Water quality parameters under optimal conditions, namely temperature 27.5-28 0C, pH 7.1-7.5, DO 4.5-5.5 ppm, NH3 0.001-0.016 ppm. Ketapang leaf extract can increase the hatchability of cork fish eggs to a concentration of 30 ppm.